Flattening the curve of electric consumption with photovoltaics and saving habits in an apartment in Lima (2017-2020) - Valdivia-Sisniegas, Richard Henry (2021)
With the lockdown imposed by Covid-19 pandemic, electricity consumption has increased for many families in Peru, as well electricity tariffs. The objective of this experience was to demonstrate the possibility of photovoltaic installations in apartments even under non-ideal conditions, in addition, to study the electricity consumption integrating gradually efficient appliances and saving habits. The article explains the monitoring of 4 years (2017-2020) in an apartment in Lima, with various photovoltaic systems for partial contribution incorporated in the façade by mean of a patented hanger, to register and compare the evolution of monthly and annual consumption using electricity billing receipts. Finally, the savings in emissions and economic returns have been calculated. The results show a considerable level of savings in electricity and even more during the “new normal”, being an opportunity for the adaptation and mitigation to climate change, and considering the change of habits in electricity consumption combined with photovoltaic energy as central axis.